Sistem Pendukung Keputusan Menentukan E-Commerce Terbaik Menggunakan Metode Topsis - Siregar, Farid Akbar; Siregar, Annisa Fadillah; Setiadi, Eka Widya Ningsih (LPPM STIKOM Tunas Bangsa, 2024)
One of the trading activities that has become increasingly popular recently is online buying and selling transactions. The development of the digital world indirectly influences the growth of online buying and selling transactions or e-commerce. This rapid growth has led to a variety of service and product offerings from various e-commerce platforms, often leaving users confused about choosing the platform that best fits their needs and availability. Users frequently face complex questions such as which platform offers the best service quality, which platform provides the most optimal transaction security, and which platform is the most reliable for transactions. Therefore, an evaluation is needed to help users assess which platform best meets their needs. This study utilizes the TOPSIS method, as this method is considered to have a simple concept in producing alternative decisions in an accurate mathematical form. The results of this study, using 5 criteria and 8 alternative e-commerce platforms, indicate that Shopee (A1) is the best alternative with a score of 0.9564.